IMPLICATURE OF CRITICISM UTTERANCES IN TROY AND KING ARTHUR MOVIES MANUSCRIPT - Ida Megawati (Universitas Sarjanawiyata Tamansiswa, 2020)
The aims of this study are to find implicature of criticism utterances, maxim, and politeness strategies of the criticizing utterances in Troy and King Arthur movies manuscript. The type of this study is a qualitative study. The data source of this study is Aristocratic movies manuscript. The methods of collecting data are documentation the movies manuscript and observation of the utterances, gathering data criticism utterances, coding the data and finding criticism utterances implied. This study shows the variety of implicatures, cooperative principles, and politeness pattern of criticizing utterances. The implicature of criticism utterances are mocking, contradiction, order, disappointment, forbid, satire, anger, and advice. The second analysis is cooperative principles by Grice. There are maxim of clarify and quantity. The politenesses of strategies are bald on record, positive and negative politeness.